2012
DOI: 10.1073/pnas.1120915109
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of carnivorism in the Ascomycota (fungi)

Abstract: Carnivorism is one of the basic life strategies of fungi. Carnivorous fungi possess the ability to trap and digest their preys by sophisticated trapping devices. However, the origin and development of fungal carnivorism remains a gap in evolution biology. In this study, five protein-encoding genes were used to construct the phylogeny of the carnivorous fungi in the phylum Ascomycota; these fungi prey on nematodes by means of specialized trapping structures such as constricting rings and adhesive traps. Our ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 55 publications
6
81
1
Order By: Relevance
“…Despite the increasing interest in dating the origin and diversification of different groups in Fungi [59], [76][79], we still lack detailed information to provide hypotheses on the evolutionary history of Ascomycota. This includes the lichenized euascomycetes, a clade that is key to understanding the evolution of symbiosis in Fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the increasing interest in dating the origin and diversification of different groups in Fungi [59], [76][79], we still lack detailed information to provide hypotheses on the evolutionary history of Ascomycota. This includes the lichenized euascomycetes, a clade that is key to understanding the evolution of symbiosis in Fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, 16 species representing six types of traps were selected, and the phylogeny of the carnivorous fungi in the phylum Ascomycota was constructed using five protein-coding genes (Yang et al, 2012). Molecular clock calibration based on two fossil records revealed that fungal carnivorism diverged from saprophytism about 419 million years ago (Mya), after the origin of nematodes about 550-600 Mya.…”
Section: (2) Evolution Of Ntf and Trapsmentioning
confidence: 99%
“…In this review, we focus on NTF, a heterogeneous group of organisms that can capture, kill and destroy nematodes. These fungi are capable of developing specific mycelial structures, so-called trapping devices (traps), to capture nematodes and then extract nutrients from them (Schmidt, Dorfelt & Perrichot, 2007;Yang et al, 2007bYang et al, , 2012. Most NTF can live both saprophytically on organic matter and as predators by capturing tiny animals (Pramer, 1964;Nordbring-Hertz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the importance of JA signaling involves a role in balancing the stress response mechanisms with plant growth, to achieve optimum growth without compromising the stress tolerance. This occurs in collaboration between the JA and gibberellin (GA) signaling pathways (Yang et al, 2012). This cross-talk is clearly important for regulation of the expression of thylakoid membrane and Calvin cycle proteins, which are upregulated in MeJA-treated GA-insensitive ( gai ) mutant compared to MeJA-treated WT (Figure 4).…”
Section: The Role Of Membrane Protein Phosphorylation In Signaling Pamentioning
confidence: 99%